Aston University's Antimicrobial Resistance (AMR) Roadshow: raising awareness and embedding knowledge of AMR in key stage 4 learners - Rabia Ahmed; Amreen Bashir; James E.P. Brown; Jonathan A.G. Cox; Anthony C. Hilton; Samantha L. Jordan; Eirini Theodosiou; Tony Worthington (Elsevier, 2020)
Summary: Antimicrobial resistance (AMR) is a global healthcare problem and therefore raising awareness within young learners is imperative. An AMR roadshow was designed to take key stage 4 students' learning 'out of the classroom', assess pre-existing knowledge of AMR and determine the impact of the roadshow on knowledge retention. Knowledge and subsequent retention were measured pre- and post-event through a standardised questionnaire. The roadshow significantly improved knowledge and understanding of AMR, which was retained for a minimum of twelve weeks. Engaging and interactive strategies addressing key health issues provide a positive learning experience which contributes to retained knowledge in young learners.